2022
DOI: 10.3390/en15072321
|View full text |Cite
|
Sign up to set email alerts
|

Direct Driven Hydraulic System for Skidders

Abstract: This paper investigates potential uses of a novel direct driven electro-hydraulic systems for articulated forestry tractors (skidders), due to these systems having notably higher energy efficiencies compared to classical electro-hydraulic systems that are currently being used in skidders for steering, lifting the front and the rear plate, as well as for operating the double-drum winch. A detailed analysis of the skidder rear plate mechanism is carried out, and static force profiles of hydraulic cylinders are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Another group of experimental studies can be identified in which the implemented hardware is limited to the power-train, including the cylinders, and the load force is emulated by applying weights or force from load cylinders. Two examples of this are [14], where static load conditions of a skidder are simulated by lifting and lowering different weight plates, and in [15], another hydraulic cylinder is used to apply a load to the tested cylinder, which the authors mention as a way of testing the performance in a realistic duty cycle. Such an approach might be sufficient to evaluate the static efficiencies of a single actuator, but realistic cycles with multiple mutually influencing actuators and realistic inertia for dynamic investigations cannot be tested.…”
Section: Experimental Approaches In Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Another group of experimental studies can be identified in which the implemented hardware is limited to the power-train, including the cylinders, and the load force is emulated by applying weights or force from load cylinders. Two examples of this are [14], where static load conditions of a skidder are simulated by lifting and lowering different weight plates, and in [15], another hydraulic cylinder is used to apply a load to the tested cylinder, which the authors mention as a way of testing the performance in a realistic duty cycle. Such an approach might be sufficient to evaluate the static efficiencies of a single actuator, but realistic cycles with multiple mutually influencing actuators and realistic inertia for dynamic investigations cannot be tested.…”
Section: Experimental Approaches In Literaturementioning
confidence: 99%
“…Furthermore, the efficiency or consumption of the whole implement system with all major actuators is of interest; thus, boom, tilt, and telescope cylinders should be present in the setup connected by the real kinematic chains. Accordingly, setting up a test rig for a single actuator as in [14][15][16][17], would not be effective. Instead, an existing conventional nine-tonne telehandler has been chosen as the test platform, which can be seen in Figure 1, to incorporate the original kinematic chains, inertia, and control interface.…”
Section: Chosen Experimental Design For Rapid Yet Realistic Testingmentioning
confidence: 99%
“…However, the main recent development direction seems to be towards the analysis of hydraulic systems having distributed valve structure and employing two-way, two-position (2/2) valves. Such systems are integrated on the level of the electric control system [24][25][26][27][28]. Attempts at developing electro-hydraulic systems with high dynamic parameters are also present in research on new electrically controlled valves [29] and on systems employing multi-chamber cylinders [30].…”
Section: Introductionmentioning
confidence: 99%